Interleukins IL-33 and IL-17/IL-17A in patients with ulcerative colitis - Ajduković, Jasna; Tonkić, Ante; Salamunić, Ilza; Hozo, Izet; Simunić, Miroslav; Bonacin, Damir (Hepato-gastroenterology, 2010)
Disturbance of immune homeostasis in ulcerative colitis (UC) is related to the predominance of T-helper-2 (Th2) immune response. Interleukin (IL)-33 stimulates Th lymphocytes to produce Th2 cytokines, such as IL-4, IL-5, and IL-13, which are believed to induce pathological changes in the intestinal mucosa. The pro-inflammatory role of IL-17 in UC is still unclear. Our aim was to determine serum concentrations of IL-33 and IL-17 in patients with UC and healthy controls. Serum concentrations of IL-33 and IL-17 were measured in 18 patients (10 men) with UC and 16 control subjects (10 men) by using two-layer immunoenzyme procedure (ELISA). Median serum concentrations of IL-33 in patients with UC and controls were 140 pg/ mL (interquartile range [IQR], 72.5 pg/mL) and 165 pg/mL (IQR, 140.0 pg/mL), respectively, but the difference was not statistically significant (Mann-Whitney U=112, p = 0.281). The median serum concentration of IL-17/IL-17A in patients with UC was significantly higher (100 pg/mL, IQR 35.75pg/mL) than that in controls (65 pg/ mL, IQR 32.25 pg/mL) (Mann-Whitney U=55, p = 0.002). Serum concentration of IL-33 in patients with UC was not increased in comparison with that in controls, which is in accordance with current evidence that its primary biological effect is transcriptional rather than cytokinal. Further research is needed to explain whether increased concentration of IL-17 in UC is protective or harmful and to elucidate its immunological and pathogenic role.